Assessoria de comunicação ao projeto TransformAção em Arte - Costa, Eloísa Barbosa da (2018)
The Experimental Project developed by the group was a Communication Assistance to the TransformAção em Arte Project, a subproject of the TransformAção Project, which works with children and adolescents in situations of social vulnerability in Vila Popular, in the city of Passo Fundo. The main objective of this advisory was to add value to the project brand, and consequently to bring new donors of school supplies, cleaning materials, clothes, food and also money, the project ends with donations. After the diagnosis, it was observed that the institution has almost no visibility in social networks as well as traditional media in Passo Fundo. From this, actions were developed that reversed this reality, mainly in the social networks, where the majority of the population step by step can be found. At the end, it was noticed that the Advice provided during these months helped increase the visualization of the Project in both the community in which it is inserted and in the social networks, after all the reverberation of the published content obtained a good engagement.